MENINGKATKAN HASIL BELAJAR SISWA TEMA 6 SUBTEMA 1 AKU DAN CITA-CITAKU MENGGUNAKAN MODEL SCRAMBLE DI KELAS IV SDN 100111 HUTA TUNGGAL - Hairani, Susi; Samakmur, Samakmur; Nasution, Sartika Rati Asmara; Batubara, Ulfah Nury (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2024)
This study aims to determine the improvement and student learning outcomes in theme 6 subthemes 1 me and my ideals using the Scramble model in class IV SDN 100111 Huta Tunggal. The type of research used is Classroom Action Research (CAR). The subjects of this study were fourth grade students at SDN 100111 Huta Tunggal. The instruments used were observation and tests to collect data. The results showed that student learning outcomes in the first cycle of scramble  were 51,53, which was in the less category. Then the second cycle of learning from observations of learning activities using the Problem Based Learning learning model obtained an average value of 77,69 which is in the good category. This achievement shows that the learning process has been going well. the learning outcomes of cycle I found that the highest score achieved by students was 90 while the lowest score was 0. The number of students who completed was 5 students or around 38%. While participants did not complete as many as 8 students or as much as 62%. Then learning cycle II is known that the highest score achieved by students is 95 while the lowest score is 40. It is known that the percentage level is 77% where there are as many as 11 students complete in cycle II learning. The number of incomplete students is 3 students or as much as 23%. This shows an increase in student outcomes from cycle I to cycle II.